LITERATURE REVIEW : HUBUNGAN ANTARA PAPARAN ORGANOFOSFAT DENGAN PARU OBSTRUKTUF - Anak Agung Istri Inten; Septi Handayani; Abi Bakring Balyas (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
WHO noted that there were 1-5 million cases of pesticide poisoning in 2014 in the argicultural enviroment. In indonesia, according to the Data Sentra Informasi Keracunan Nasional in 2016, there were 771 cases of pesticide poisoning. Organophosphate pesticides can enter the body through inhalation, ingestion, and dermal contact. Organophosphate have a toxic effect on the respiratory system, which can cause obstructive pulmonary disorders. The purpose of this literature review is to determine a relationship between organophosphate exposure and obstructive pulmonary disorders. This literature review research uses a systematic literature review. The research sample is secondary data in the form of articles obtained from Google Scholar and Research Gate with the keywords organophosphates, obstructive pulmonary disorder, and FEV1 which were published in 2011-2021 where 18 journals met the inclusion criteria consisting of 4 national journals and 14 international journals. From 18 journals, 16 journals stated that there was a relationship between exposure to organophosphates and obstructive pulmonary disorders and 2 journals said that there was no relationship between exposure to organophosphates and impaired lung function. Based on the results of this literature review, it was found that there was a relationship between exposure to organophosphates and obstructive pulmonary disorders of 88.9% and 11.1% unrelated.